A Concept of Upgrading the Content of Mother Language Education - ugli, Zokirov Javohir Gaybullo (Researchparks Publishing, 2023)
In the article, updating the content of mother tongue education, the structure of modern mother tongue textbooks, activation of work on introducing innovative approaches to teaching mother tongue through educational tasks; improvement of scientific, methodical, psychological and pedagogical support system development for mother tongue teaching; It is thought about the important task of today to involve the latest achievements of ethnolinguistics in the educational process.